2020
DOI: 10.4067/s0717-97072020000204849
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF WATER-SOLUBLE COMPOUNDS CONTAINED IN AQUEOUS EXTRACTS AND FRACTIONS OBTAINED FROM LEAVES OF Ugni Molinae TO DETERMINE THEIR EFFECT ON THE VIABILITY OF HUMAN GASTRIC CANCER CELLS

Abstract: Ugni molinae Turcz. Myrtaceae (Murtilla) is a plant native to Chile. There is evidence about the antiproliferative compounds present in fruits, but there is no evidence on the antiproliferative activity of the compounds in the leaves. These compounds have importance because they predominate in the popular form of ingestion of leaves. In the present study, the identification of water-soluble components of leaves of U. molinae and a fractionation were carried out to determine the effect on viability of gastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…Braganca De Moraes et al (2012) reported that catechin inhibited the proliferation of GRX liver cells, attributing the action to the inhibition of inflammation and the cell cycle. Additionally, Abd-Rabou et al (2016) found anticarcinogenic ellagic and gallic acids to be cytotoxic mediators against HepG2 and HCT 116 cell lines and decreasing viable human colon tumor cells; Flis et al (2012) showed the effectiveness of antioxidant murta berry extracts-correlated with its phenols-against colon cancer cell lines; Avello et al (2020) found that total aqueous murta leaf extract had synergistic effects in inhibiting cell viability against gastric adenocarcinoma cells (AGS) and that the metabolites of some elements even inhibited the viability of Caco-2 cells.…”
Section: Anti-tumoral Activitymentioning
confidence: 99%
“…Braganca De Moraes et al (2012) reported that catechin inhibited the proliferation of GRX liver cells, attributing the action to the inhibition of inflammation and the cell cycle. Additionally, Abd-Rabou et al (2016) found anticarcinogenic ellagic and gallic acids to be cytotoxic mediators against HepG2 and HCT 116 cell lines and decreasing viable human colon tumor cells; Flis et al (2012) showed the effectiveness of antioxidant murta berry extracts-correlated with its phenols-against colon cancer cell lines; Avello et al (2020) found that total aqueous murta leaf extract had synergistic effects in inhibiting cell viability against gastric adenocarcinoma cells (AGS) and that the metabolites of some elements even inhibited the viability of Caco-2 cells.…”
Section: Anti-tumoral Activitymentioning
confidence: 99%
“…Los berries han sido catalogados como frutos con importantes propiedades beneficiosas para la salud humana (Avello, Pastene, Bustos, Bittner, & Becerra, 2013;Riquelme et al, 2014), los cuales son asociados a la defensa de diferentes patologías y aplicaciones en el tratamiento y prevención del cáncer. por ejemplo, se ha demostrado que los componentes hidrosolubles de hojas de Ugni molinae tienen efecto sobre la viabilidad de células de cáncer gástrico en humanos (Arancibia-Radich et al, 2016;Avello, Pastene, & Eillen, 2020;Goity et al, 2013); así como las actividades biológicas, antimicrobianas y antioxidantes (López de Dicastillo et al, 2017). En los extractos de semilla de murta se encuentran presentes metabolitos secundarios tales como ácidos fenólicos, flavonoides y taninos, considerados como precursores de defensa contra el ataque de patógenos relacionadas con la salud humana y alimentaria (Cabrera-Barjas et al, 2020).…”
Section: Introductionunclassified